Effect of catalyst loading on Ni/ZrO2 activity for methane steam reforming at low temperature - Nguyen, Long Quang (Animo Repository, 2006)
Continuing the research on the catalysis process for natural gas utilization under AUN/SEED-Net project, this study focused on the effect of Ni loading on ZrO2 for low temperature Methane Steam Reforming (MSR). The ZrO2-supported catalysts which contained 10%, 15%, 20%, 25%, and 30% Ni were prepared by impregnation method and labeled Ni10, Ni15, Ni20, Ni25, Ni30 respectively. They were characterized using AAS, XRD, EDX, SEM, and BET methods. The acidity and basicity of the catalysts were determined using NH3-TPD and CO2-TPD respectively. The catalytic activity was tested at 6000C, GHSV of 24,000 h-1, and ratio of H2O/CH4 equal to 3. The results of AAS reported that the catalysts contained the Ni loading from 9.45% to 27.71%. The XRD results confirmed the monoclinic structure of the support and the presence of nickel zero valence. The elemental composition on the surface increased when the Ni loading increased. The surface areas and the pore volume of the catalysts decreased when the nickel loading increased, while the values of average pore-size retained almost unchanged. The increase of the nickel loading led to a decrease in basicity and also acidity. The number of basic sites was much greater than the number of acidic site for all of the catalysts tested. Among the tested catalysts, the sample Ni15, which contained actually 14.37% Ni, performed the highest methane conversion of 80.95% and best stability in 8 hours reaction. The sample Ni10 showed also a good stability but the average methane conversion was 77.84%. The others which contained higher Ni showed high methane conversion at the induction but the conversions gradually decreased towards the end of the testing time. The hydrogen yields were almost stable for all catalysts. The higher values were obtained at samples Ni10, and Ni15. However, the highest H2/CO ratio obtained at the iv sample Ni20. The selectivity of CO and CO2 in the results of samples Ni10 and Ni15 was stable during the testing time but that of the others. The amount of coke generated on the samples Ni10 and Ni15 were much smaller than those found on the higher nickel loading samples.